Schmallenberg virus SBV infection among small ruminants in selected states of Peninsular Malaysia - Abdullah Jesse, Faez Firdaus; Paul, Bura Thlama; Hashi, Hamza Abdirahman; Lim, Eric Teik Chung; Muhamad Sedeka, Nur Iffah Husna; Mohd Lila, Mohd Azmi (Assiut University, Faculty of Veterinary Medicine, Department of Animal Medicine, 2022)
Schmallenberg virus (SBV) is an emerging arthropod-borne pathogen of domestic and wild ruminants responsible for devasting economic losses in European countries with a potential for spreading across boundaries. Three hundred sixty-two (362) serum samples were randomly collected from 7 selected sheep and goat farms from January to October 2019 to investigate the seroprevalence of SBV among small ruminants in Negeri Sembilan and Terengganu states. Seroprevalence of SBV was determined using commercial ID vetÂ®Â SBV multispecies cELISA test. The farmers completed a structured questionnaire to furnish farm management data to evaluate the risk factors associated with the seroprevalence of SBV among individual animals. A Chi-square test was performed to determine the association between seroprevalence of SBV and putative risk factors of individual animals. Based on the ELISA test, a total of 78 individual animals were seropositive with an overall prevalence of 21.5% and the true prevalence of 22.1% (95% CI:18.06-26.71). Multivariable logistic regression analysis further revealed that Negeri Sembilan state (p<0.001; OR=14.290; 95% CI=5.384-37.930), Breed: Malin sheep (p<0.001; OR=20.453; 95% CI=4.807-87.022), Barbados Black Belly sheep (p<0.01; OR=69.947; 95% CI=16.819-290.901), Boer goat (p<0.001; OR=9.108; 95% CI=3.191-25.997) and crossbred goat (p=0.001; OR=4.964; 95% CI=1.905-12.934) are risk factors of SBV among individual animals. This study highlights the prevalence of a new transboundary disease among small ruminants in Malaysia. The result obtained here provides preliminary data that could guide livestock producers and policy makers in designing suitable prevention and control measures.